Determining factors affecting perceived quality among shoe manufacturing workers towards shoe quality: A structural equation modeling approach - Thanatorn Chuenyindee; Robimarl B. Torres; Yogi Tri Prasetyo; Reny Nadlifatin; Satria Fadil Persada (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The shoe industry has been continuously growing in recent years. The goal of this study was to identify factors affecting perceived shoe quality among shoe manufacturing workers. A sample of 350 shoe manufacturing workers participated in answering a survey that was distributed using a purposive sampling approach. Structural Equation Modeling (SEM) indicated that quality training was the most significant factor on perceived shoe quality, indicating that quality training should be prioritized and included in company programs to sustain quality products. Interestingly, perceived tooling/machinery conditions, teamwork and cooperation, the operator's technical skills, and the operator's quality mindset, also had significant effects on perceived shoe quality. This study is one of the first studies to explore perceived shoe quality among shoe manufacturing workers. The results may convey information for future research on perceived product quality, particularly for the shoe industry. Finally, our framework can be utilized for the enhancement of perceived product quality in shoe manufacturing industries worldwide.
Keywords: 650; perceived quality; shoe quality; Structural Equation Modeling